Alergeni in sprožilci alergijskih dogajanj - Čamernik, Maja (Slovenska pediatrija, 2010)
There has been a significant increase in allergic diseases in the past few years. They affect 20-30% of the population. In most cases their onset is in adolescence or even in early childhood. Over the years most allergies mitigateor even disappear. However, some are persistent or even lifelong. Allergic reactions can be caused by direct contact with an allergen or allergens (ingested or inhaled). Socalled allergy triggers, including smoke, cosmetic products, emotional shocks and physical strain, can also provoke allergy symptoms.
Keywords: Alergeni; alergija; Allergens; Bee Venoms; Classification; Čebelji strupi; Food Hypersensitivity; hrana; Hrana, preobčutljivost; Hypersensitivity; Osji strupi; piki žuželk; Preobčutljivost; Wasp Venoms